Composite diaphragm and preparation method thereof

By applying composite separator design on lithium-ion battery separator, using the combination of ceramic coating and functional coating, the problem of easy dissolution of the separator in high-temperature environment and insufficient puncture strength is solved, and higher high temperature resistance and puncture resistance are achieved, which significantly optimizes the electrochemical performance of the battery.

CN119742532AActive Publication Date: 2025-04-01东莞维科电池有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411728553.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-01
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators are easily dissolved in high temperature environments, which may lead to short circuits inside the battery, and there are shortcomings in the puncture strength of the ceramic coated separators.

Method used

It adopts a composite diaphragm design, including base film, ceramic coating and functional coating. The functional coating consists of a binder, lithium titanium aluminum phosphate and lithium poly-2-acrylamide-2-methylpropanesulfonate. Through the combination of these materials, the membrane's high temperature resistance, puncture resistance and electrochemical properties are enhanced.

Benefits of technology

It significantly improves the high temperature resistance and puncture resistance of the diaphragm, alleviates the battery's self-discharge problem, and optimizes the electrochemical performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742532A_ABST
    Figure CN119742532A_ABST
Patent Text Reader

Abstract

The invention discloses a composite diaphragm and a preparation method thereof, and the composite diaphragm is provided with a functional coating of lithium titanium aluminum phosphate and poly-2-acrylamide-2-lithium methylpropanesulfonate, so that the performance of the composite diaphragm is obviously improved. The lithium titanium aluminum phosphate can spontaneously form a layer of protective film in a low-potential environment, and the layer of film can effectively prevent lithium dendrites from puncturing the diaphragm, so that the problem of serious self-discharge of the diaphragm battery is greatly relieved. The added poly-2-acrylamide-2-methyl propanesulfonic acid lithium shows high binding energy with Li < + >, which not only promotes the Li < + > to easily break away from the constraint of a solvent sheath, but also significantly improves the ionic conductivity of the diaphragm, effectively reduces the dissolving energy barrier, and ensures the high reversibility of the lithium deposition process. In addition, due to the addition of the binder, coating substances are tightly connected, and the three substances supplement each other, so that the puncture resistance of the composite diaphragm is remarkably enhanced, and the electrochemical performance of the lithium ion battery is greatly optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a composite diaphragm and a preparation method thereof. Background Art

[0002] As the most common type of commercial secondary battery, lithium-ion batteries have been widely used in various electronic devices and power batteries due to their excellent energy density, extremely low self-discharge rate and excellent cycle life. The core structure of the battery includes four major components: positive electrode, negative electrode, diaphragm and electrolyte. Among them, the diaphragm plays a vital role. It not only effectively isolates the positive and negative electrodes to prevent direct contact, but also has the function of transmitting ions. It is a key component to ensure the safe and stable operation of the battery.

[0003] With the diversified development of electronic products and the continuous expansion of the application field of power batteries, the market has put forward more stringent requirements on the performance of lithium-ion batteries, which has indirectly prompted the demand for further improvement of the performance of diaphragm materials. Traditionally, commercial diaphragms are mainly made of polyolefin materials such as polyethylene, polypropylene or their composite materials. However, such materials are prone to dissolution in high temperature environments, which may cause internal short circuits in the battery and thus cause safety hazards.

[0004] In order to overcome the shortcomings of polyolefin separators under high temperature conditions, the industry has tried to improve them by uniformly coating one or both sides of the polyolefin separator with a ceramic layer. This ceramic-coated separator significantly enhances the high temperature resistance of the separator and improves the overall safety of the battery. Nevertheless, current ceramic separators still have limitations in terms of puncture strength, that is, their ability to maintain structural integrity when punctured by sharp objects needs to be strengthened.

[0005] In view of the above-mentioned defects of the current diaphragms, it is indeed necessary to provide a technical solution to the above-mentioned problems. Summary of the invention

[0006] The purpose of the present invention is to provide a composite diaphragm, which has high temperature resistance, high safety and good puncture performance.

[0007] In order to achieve this object, the present invention provides the following scheme:

[0008] A composite diaphragm, comprising:

[0009] Basement membrane;

[0010] A ceramic coating is disposed on at least one surface of the base film;

[0011] The functional coating comprises a binder, lithium aluminum titanium phosphate and lithium poly-2-acrylamide-2-methylpropane sulfonate; and is arranged on a surface of the base film and / or a surface of the ceramic coating.

[0012] Preferably, the molecular weight of the poly-2-acrylamide-2-methylpropanesulfonate lithium is 20,000-40,000, and the degree of polymerization is 96-194.

[0013] Preferably, the mass ratio of the binder, the lithium aluminum titanium phosphate and the lithium poly-2-acrylamide-2-methylpropane sulfonate is 0.1-10:20-80:0.5-15.

[0014] Preferably, the thickness ratio of the base film, the functional coating and the ceramic coating is 4-5:1-3:1-2.

[0015] Preferably, the base film has a thickness of 4 to 5 μm, the functional coating has a thickness of 1 to 3 μm, and the ceramic coating has a thickness of 1 to 2 μm.

[0016] Preferably, the binder is at least one of polyvinylidene fluoride and polymethyl methacrylate; the chemical formula of lithium aluminum titanium phosphate is Li (1+x) Al x Ti (2-x) , X satisfies the relationship: 0.2≤X≤0.9. The particle size D50 of lithium aluminum titanium phosphate is 0.1 μm-1.0 μm, preferably 0.2 μm-0.3 μm.

[0017] The present invention also provides a method for preparing a composite diaphragm, comprising the following steps:

[0018] Step 1: dissolving ceramic particles and a binder in a solvent, dispersing them evenly, and preparing a ceramic coating slurry, coating the ceramic coating slurry on at least one surface of a base film, and drying to obtain a ceramic coating;

[0019] Step 2: Weigh 2-acrylamide-2-methylpropanesulfonic acid and azobisisobutyronitrile, add to NMP, heat and stir, add Li2CO3 powder, continue heating and stirring, and react to obtain a solution A containing lithium poly-2-acrylamide-2-methylpropanesulfonate;

[0020] Step 3: dispersing the binder and lithium aluminum titanium phosphate in a solvent to obtain a solution B; stirring and mixing the solution A with the solution B twice to obtain a functional coating slurry;

[0021] Step 4: coating the functional coating slurry on the other surface of the base film and / or the surface of the ceramic coating, drying, obtaining a functional coating, and obtaining a composite diaphragm.

[0022] Preferably, in step 1 and step 3, the solvent is at least one of acetonitrile, chloroform, dichloroethane, dimethylformamide, N-methylpyrrolidone and tetrahydrofuran.

[0023] Preferably, in step one, the adhesive includes at least one of polyethylene oxide, polyacrylic acid, and polyvinylidene fluoride.

[0024] Preferably, in step 1, the ceramic particles are selected from AlO3 and boehmite.

[0025] Preferably, in step one, the mass percentage of the binder in the ceramic coating slurry is 1 to 10 wt %; the mass percentage of the ceramic particles in the ceramic coating slurry is 20 to 60 wt %; and the mass percentage of the solvent in the ceramic coating slurry is 40 to 70 wt %.

[0026] Preferably, in the step 2, the mass ratio of the 2-acrylamide-2-methylpropanesulfonic acid, the azobisisobutyronitrile and the Li2CO3 powder is 60-80:1-5:20-30.

[0027] Preferably, in the step 2, the mass concentration of the lithium poly-2-acrylamide-2-methylpropane sulfonate in the solution A is 10% to 50%.

[0028] Preferably, in the step three, the mass ratio of the lithium aluminum titanium phosphate, the binder and the lithium poly-2-acrylamide-2-methylpropane sulfonate is 3-5:0.5-2:0.5-2.

[0029] Preferably, the solid content of the ceramic coating slurry and the functional coating slurry is 5% to 40%.

[0030] Preferably, in step 2 and step 3, the stirring temperature is 25°C to 60°C.

[0031] The present invention also provides a secondary battery, comprising a diaphragm, a negative electrode sheet, an electrolyte, a battery shell and a positive electrode sheet, wherein the diaphragm is the above-mentioned composite diaphragm.

[0032] Compared with the prior art, the beneficial effect of the present invention is that the present invention achieves a significant improvement in performance by providing a functional coating of lithium aluminum titanium phosphate and lithium poly-2-acrylamide-2-methylpropane sulfonate on the surface of the diaphragm. Specifically, lithium aluminum titanium phosphate can spontaneously form a protective film under low potential conditions, which can effectively prevent lithium dendrites from piercing the diaphragm, thereby greatly alleviating the serious self-discharge problem of the diaphragm battery. At the same time, the added lithium poly-2-acrylamide-2-methylpropane sulfonate and Li +exhibited high binding energy, which not only promoted the + It can easily break away from the constraints of the solvent sheath, significantly improve the ionic conductivity of the separator, and effectively reduce the dissolution energy barrier, ensuring the high reversibility of the lithium deposition process. In addition, the addition of the binder makes the coating material closely connected to form a stable whole. These three complement each other, not only significantly enhancing the puncture resistance of the composite separator, but also greatly optimizing the electrochemical performance of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a test data chart of the capacitance retention rate of the lithium ion batteries of Examples 1 to 8 of the present invention and Comparative Examples 1 to 4. DETAILED DESCRIPTION

[0034] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] According to a first aspect of the present invention, there is provided a composite diaphragm, comprising:

[0036] Basement membrane;

[0037] A ceramic coating is disposed on at least one surface of the base film;

[0038] The functional coating comprises a binder, lithium aluminum titanium phosphate and lithium poly-2-acrylamide-2-methylpropane sulfonate; and is arranged on a surface of a base film and / or a surface of a ceramic coating.

[0039] The present invention achieves significant performance improvement by adding lithium aluminum titanium phosphate and lithium poly-2-acrylamide-2-methylpropane sulfonate to the functional coating of the diaphragm. Specifically, lithium aluminum titanium phosphate can spontaneously form a protective film under low potential environment, which can effectively prevent lithium dendrites from piercing the diaphragm, thereby greatly alleviating the serious self-discharge problem of diaphragm batteries. At the same time, the added lithium poly-2-acrylamide-2-methylpropane sulfonate and Li + exhibited high binding energy, which not only promoted the + It can easily break away from the constraints of the solvent sheath, significantly improve the ionic conductivity of the separator, and effectively reduce the dissolution energy barrier, ensuring the high reversibility of the lithium deposition process. In addition, the addition of the binder makes the coating material closely connected to form a stable whole. These three complement each other, not only significantly enhancing the puncture resistance of the composite separator, but also greatly optimizing the electrochemical performance of lithium-ion batteries.

[0040] In one embodiment of the present invention, the molecular weight of lithium poly-2-acrylamide-2-methylpropanesulfonate is 20000-40000, for example, 20000, 25000, 30000, 35000, 40000; the degree of polymerization is 96-194, for example, 96, 97, 98, 99, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 194. The molecular weight and degree of polymerization of lithium poly-2-acrylamide-2-methylpropanesulfonate are similar to Li + exhibited high binding energy, which not only promoted the + It can easily break away from the constraints of the solvent sheath, significantly improve the ionic conductivity of the separator, and effectively reduce the dissolution energy barrier, ensuring the high reversibility of the lithium deposition process. If the molecular weight or degree of polymerization exceeds this, the thorn effect cannot be achieved.

[0041] In one embodiment of the present invention, the mass ratio of the binder, lithium aluminum titanium phosphate and lithium poly-2-acrylamide-2-methylpropane sulfonate is 0.1-10:20-80:0.5-15, for example, it can be 0.1:20:0.5, 0.1:30:0.5, 0.1:40:0.5, 0.1:50:0.5, 0.1:60:0.5, 0.1:70:0.5, 0.5:20:1, 1:20:0.5, 2:20:0.5, 3:20:0.5, 4:20:0.5, 5:20:0.5, 6:20:0.5, 7:20:0.5, 8:20:0.5, 9:20:0.5, 10:20:0.5, 0.1:20:1, 2:20:2, 3:20:2, 4:20:2, 5:20:5, 6:20:5, 7:20:5, 8:20:8, 9:20:8, 10:20:9.

[0042] In one embodiment of the present invention, the thickness ratio of the base film, the functional coating and the ceramic coating is 4-5:1-3:1-2, for example, 4:1:1, 4.5:1:1, 5:1:1, 4:2:1, 4:3:1, 4:1:2. The base film, as a supporting layer, has a thicker thickness, which provides good mechanical strength and stability, and helps to resist external pressure and impact. Although the functional coating and the ceramic coating are thin, their presence further enhances the overall mechanical properties, especially in terms of high temperature resistance and puncture resistance.

[0043] In one embodiment of the present invention, the thickness of the base film is 4 to 5 μm, for example, it can be 4 μm, 4.1 μm, 1.2 μm, 1.3 μm, 4.4 μm, 4.5 μm, 1.6 μm, 4.7 μm, 4.8 μm, 4.9 μm, and 5 μm; the thickness of the functional coating is 1 to 3 μm, for example, it can be 1 μm, 1.1 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.8 μm, 1.9 μm, 2 μm, 2.2 μm, 2.5 μm, 2.8 μm, 2.9 μm, and 3 μm; the thickness of the ceramic coating is 1 to 2 μm, for example, it can be 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, and 2 μm.

[0044] In one embodiment of the present invention, the binder is at least one of polyvinylidene fluoride and polymethyl methacrylate; the chemical formula of lithium aluminum titanium phosphate is Li (1+x) Al x Ti (2-x) , X satisfies the relationship: 0.2≤X≤0.9, for example, it can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, preferably 0.7. The particle size D50 of lithium aluminum titanium phosphate is 0.1μm-1.0μm, preferably 0.2μm-0.3μm. For example, it can be 0.21μm, 0.22μm, 0.23μm, 0.24μm, 0.25μm, 0.26μm, 0.27μm, 0.28μm, 0.29μm, 0.3μm. Lithium aluminum titanium phosphate with a particle size D50 in the range of 0.2μm to 0.3μm has a larger specific surface area, thereby increasing the contact area with the electrolyte, improving the utilization rate of the active material, and also helping to reduce the polarization phenomenon of the battery, especially during high current charging and discharging. This helps to maintain the stability of the battery and extend the service life of the battery. In addition, lithium aluminum titanium phosphate can spontaneously form a protective film under low potential environment, which can effectively prevent lithium dendrites from puncturing the diaphragm, thereby greatly alleviating the serious self-discharge problem of diaphragm batteries.

[0045] In a second aspect of the present invention, a method for preparing a composite membrane is also provided, comprising the following steps:

[0046] Step 1: dissolving ceramic particles and a binder in a solvent, dispersing them evenly, and preparing a ceramic coating slurry, coating the ceramic coating slurry on at least one surface of the base film, and drying to obtain a ceramic coating;

[0047] Step 2: Weigh 2-acrylamide-2-methylpropanesulfonic acid and azobisisobutyronitrile, add to NMP, heat and stir, add Li2CO3 powder, continue heating and stirring, and react to obtain a solution A containing lithium poly-2-acrylamide-2-methylpropanesulfonate;

[0048] Step 3: Dispersing the binder and lithium aluminum titanium phosphate in a solvent to obtain solution B; stirring and mixing solution A with solution B twice to obtain a functional coating slurry;

[0049] Step 4: coating the functional coating slurry on the other surface of the base film and / or the surface of the ceramic coating, drying, obtaining the functional coating, and obtaining the composite diaphragm.

[0050] In one embodiment of the present invention, in step 1 and step 3, the solvent is at least one of acetonitrile, chloroform, dichloroethane, dimethylformamide, N-methylpyrrolidone and tetrahydrofuran.

[0051] In one embodiment according to the present invention, in step one, the adhesive includes at least one of polyethylene oxide, polyacrylic acid, and polyvinylidene fluoride.

[0052] In one embodiment according to the present invention, in step 1, the ceramic particles are selected from AlO 3 and boehmite.

[0053] In one embodiment according to the present invention, in step one, the mass percentage of the binder in the ceramic coating slurry is 1-10wt%, for example, it can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%; the mass percentage of the ceramic particles in the ceramic coating slurry is 20-60wt%, for example, it can be 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%; the mass percentage of the solvent in the ceramic coating slurry is 40-70wt%, for example, it can be 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%.

[0054] In one embodiment of the present invention, in step 2, the mass ratio of 2-acrylamide-2-methylpropanesulfonic acid, azobisisobutyronitrile and Li2CO3 powder is 60-80:1-5:20-30. 2-acrylamide-2-methylpropanesulfonic acid is a polymer. Synthesis The main material of poly-2-acrylamide-2-methylpropane sulfonic acid, accounts for a large proportion; azobisisobutyronitrile is an azo-type free radical initiator, and the amount of it and poly-2-acrylamide-2-methylpropane sulfonic acid added is related to the proportion of the initiator. Too much or too little initiator will affect the molecular weight and degree of polymerization of the generated polymer, which will affect the coating viscosity, mechanical strength, porosity, ion conductivity and other aspects of the subsequently prepared diaphragm; the Li2CO3 content should not be too high. Too much lithium carbonate in the diaphragm will have a negative impact on the performance, safety, consistency and production cost of the battery.

[0055] In one embodiment of the present invention, in step 2, the mass concentration of lithium poly-2-acrylamide-2-methylpropane sulfonate in solution A is 10% to 50%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%. If the mass concentration of lithium poly-2-acrylamide-2-methylpropane sulfonate is too low, the amount of other substances added in the subsequent steps will be too much; and if the concentration is too high, it is not conducive to the smooth progress of the subsequent stirring process and the uniform dispersion of the materials.

[0056] In one embodiment of the present invention, in step three, the mass ratio of lithium aluminum titanium phosphate, binder and lithium poly-2-acrylamide-2-methylpropane sulfonate is 3-5:0.5-2:0.5-2.

[0057] When the mass ratio of lithium aluminum titanium phosphate is in the range of 3 to 5, it can show good ion conductivity, mechanical stability and thermal stability. When the amount of lithium aluminum titanium phosphate is too much or too little, it will affect the ion conductivity, mechanical stability and thermal stability of the diaphragm. Excessive addition of LATP will also increase the investment cost. When the mass ratio of the binder is in the range of 0.5 to 2, the slurry is stirred evenly and the coating has good consistency. When the amount of lithium aluminum titanium phosphate is too much or too little, the slurry viscosity will be affected, which will affect the uniformity of the slurry, the consistency of the coating, and the mechanical properties. When the amount of lithium poly-2-acrylamide-2-methylpropane sulfonate is too much or too little, it will affect the ion conductivity and mechanical stability of the diaphragm.

[0058] In one embodiment of the present invention, the solid content of the ceramic coating slurry and the functional coating slurry is 5% to 40%, for example, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%. When the solid content is within this range, the stirring, coating and drying efficiency of the slurry is relatively good, which can save time and energy, thereby improving production efficiency; if the solid content is too low, the solid component in the slurry is less, and in order to achieve the required coating thickness, more slurry and longer drying time may be required, thereby increasing production costs and time; when the solid content is too high, the viscosity of the slurry is large, the fluidity of the slurry is poor, and it is difficult to form a uniform and continuous coating on the electrode, thereby affecting the performance and service life of the product.

[0059] In one embodiment of the present invention, in step 2 and step 3, the stirring temperature is 25° C. to 60° C., for example, 25° C., 30° C., 35° C., 40° C., 45° C., 50° C., 55° C., 60° C. Heating and stirring can accelerate the dissolution of the powder and make the slurry more evenly dispersed.

[0060] The present invention also provides a secondary battery, comprising a diaphragm, a negative electrode sheet, an electrolyte, a battery casing and a positive electrode sheet, wherein the diaphragm is the above-mentioned composite diaphragm.

[0061] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, and the positive electrode active material layer may include but is not limited to lithium cobalt dioxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium iron phosphorus oxide and lithium iron phosphate, etc. The positive electrode current collector may be any material suitable for use as a positive electrode current collector for lithium-ion batteries in the art, for example, aluminum foil, copper foil, nickel foil, stainless steel or carbon material.

[0062] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode active material layer can be one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium.

[0063] The graphite may be selected from one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material may be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites and silicon alloys; the tin-based material may be selected from one or more of elemental tin, tin oxide compounds and tin alloys. The negative electrode current collector is usually a structure or part for collecting current. The negative electrode current collector may be any material suitable for use as a negative electrode current collector for secondary batteries in the art. For example, the negative electrode current collector may include but is not limited to metal foil, and more specifically may include but is not limited to copper foil.

[0064] The secondary battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; it can also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.

[0065] The present invention will be further described below by means of specific examples.

[0066] Example 1

[0067] Preparation of composite diaphragm:

[0068] Step 1: dissolve 30g of aluminum oxide and 2g of polyacrylic acid in 70mL of acetonitrile, disperse them evenly, and prepare a ceramic coating slurry. Apply the ceramic coating slurry on one surface of the base film, and dry it to obtain a ceramic coating. The thickness of the ceramic coating is 1μm.

[0069] Step 2: Weigh 20g of 2-acrylamide-2-methylpropane sulfonic acid, 0.4g of azobisisobutyronitrile and 7g of Li2CO3 powder in a ratio of 73:1.5:25.5, add 2-acrylamide-2-methylpropane sulfonic acid and azobisisobutyronitrile to 80mL of NMP, heat and stir at 60°C, add Li2CO3 powder, continue heating and stirring at 60°C, and react to obtain solution A containing lithium poly-2-acrylamide-2-methylpropane sulfonate; wherein the mass concentration of lithium poly-2-acrylamide-2-methylpropane sulfonate in solution A is 23%.

[0070] Step 3: Disperse PVDF and lithium aluminum titanium phosphate in 300 mL of acetonitrile to obtain solution B; stir and mix solution A with solution B twice to obtain a functional coating slurry; wherein the weight ratio of LATP, lithium poly-2-acrylamide-2-methylpropane sulfonate, and PVDF is 4:1:1.

[0071] Step 4: coating the functional coating slurry on the other surface of the base film, drying it, obtaining a functional coating, and obtaining a composite diaphragm.

[0072] Preparation of secondary batteries:

[0073] The negative electrode sheet, the positive electrode sheet and the composite separator are interlaced and then packaged with an aluminum-plastic film to prepare a battery cell, which is placed in a battery shell, an electrolyte is added, and then sealed to obtain a lithium-ion battery. The active material of the negative electrode sheet is graphite; the active material of the positive electrode sheet is the composite positive electrode material.

[0074] Table 1 shows the data of Examples 1 to 10 and Comparative Examples 1 to 4, and the rest is the same as Example 1, which will not be described again.

[0075] Table 1

[0076]

[0077] Performance Test:

[0078] The composite diaphragms of Examples 1 to 10 and Comparative Examples 1 to 4 were subjected to diaphragm puncture performance tests, and the test results are shown in Table 2;

[0079] The secondary batteries of Examples 1 to 10 and Comparative Examples 1 to 4 were subjected to a self-discharge rate test, and the test results are shown in Table 2;

[0080] The secondary batteries of Examples 1 to 8 and Comparative Examples 1 to 4 were subjected to electrochemical performance tests. The test results were Figure 1 .

[0081] Table 2

[0082] Group K value (mv / h) Diaphragm puncture performance (gf) Example 1 0.066 186 Example 2 0.0561 192 Implementation 3 0.0451 194 Example 4 0.035 196 Example 5 0.0391 201 Example 6 0.0219 231 Example 7 0.0391 203 Example 8 0.0201 250 Example 9 0.08 176 Example 10 0.075 180 Comparative Example 1 0.137 150 Comparative Example 2 0.129 156 Comparative Example 3 0.109 161 Comparative Example 4 0.09 169

[0083] As shown in the test data in Table 2, the data of the puncture performance and K value of the diaphragm of Examples 1 to 10 are better than those of Comparative Examples 1 to 4, indicating that the present invention has achieved a significant improvement in performance by adding lithium aluminum titanium phosphate and lithium poly-2-acrylamide-2-methylpropane sulfonate to the functional coating of the diaphragm. Specifically, lithium aluminum titanium phosphate can spontaneously form a protective film under low potential conditions, which can effectively prevent lithium dendrites from puncturing the diaphragm, thereby greatly alleviating the serious self-discharge problem of the diaphragm battery. At the same time, the added lithium poly-2-acrylamide-2-methylpropane sulfonate and Li + exhibited high binding energy, which not only promoted the + It can easily break away from the constraints of the solvent sheath, significantly improve the ionic conductivity of the separator, and effectively reduce the dissolution energy barrier, ensuring the high reversibility of the lithium deposition process. In addition, the addition of the binder makes the coating material closely connected to form a stable whole. These three complement each other, not only significantly enhancing the puncture resistance of the composite separator, but also greatly optimizing the electrochemical performance of lithium-ion batteries.

[0084] like Figure 1 It can be seen from the test data shown that the test data of the capacitance retention rate of Examples 1 to 10 under the storage conditions of 60°C and 28 days are better than those of Comparative Examples 1 to 4, indicating that a functional coating is provided on the diaphragm, and when the diaphragm is used in a battery, the test data of the capacitance retention rate of the diaphragm under the storage conditions of 60°C and 28 days can be improved.

[0085] The K value range of Examples 1 to 10 is ≤ 0.08, and the K value range of Comparative Examples 1 to 4 is > 0.08. Under high temperature conditions, the chemical reaction inside the battery is accelerated, and the self-discharge reaction is also enhanced. The poor K value of Comparative Examples 1 to 4 means that the self-discharge rate of the battery is abnormal, which may cause the battery capacity to decay rapidly during high-temperature storage.

[0086] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A composite diaphragm, characterized in that: include: Basement membrane; A ceramic coating is disposed on at least one surface of the base film; The functional coating comprises a binder, lithium aluminum titanium phosphate and lithium poly-2-acrylamide-2-methylpropane sulfonate; and is arranged on a surface of the base film and / or a surface of the ceramic coating.

2. The composite diaphragm according to claim 1, characterized in that: The molecular weight of the poly-2-acrylamide-2-methylpropanesulfonate lithium is 20000-40000, and the degree of polymerization is 96-194.

3. The composite diaphragm according to claim 1, characterized in that: The mass ratio of the binder, the lithium aluminum titanium phosphate and the lithium poly-2-acrylamide-2-methylpropane sulfonate is 0.1-10:20-80:0.5-15.

4. The composite diaphragm according to claim 1, characterized in that: The thickness ratio of the base film, the functional coating and the ceramic coating is 4-5:1-3:1-2.

5. The composite diaphragm according to claim 1, characterized in that: The thickness of the base film is 4-5 μm, the thickness of the functional coating is 1-3 μm, and the thickness of the ceramic coating is 1-2 μm.

6. The composite diaphragm according to claim 1, characterized in that: The chemical formula of the lithium aluminum titanium phosphate is Li (1+x) Al x Ti (2-x) , X satisfies the relationship: 0.2≤X≤0.

9.

7. A method for preparing a composite diaphragm, characterized in that: The following steps are involved: Step 1: dissolving ceramic particles and a binder in a solvent, dispersing them evenly, and preparing a ceramic coating slurry, coating the ceramic coating slurry on at least one surface of a base film, and drying to obtain a ceramic coating; Step 2: Weigh 2-acrylamide-2-methylpropanesulfonic acid and azobisisobutyronitrile, add to NMP, heat and stir, add Li2CO3 powder, continue heating and stirring, and react to obtain a solution A containing lithium poly-2-acrylamide-2-methylpropanesulfonate; Step 3: dispersing the binder and lithium aluminum titanium phosphate in a solvent to obtain a solution B; stirring and mixing the solution A with the solution B twice to obtain a functional coating slurry; Step 4: coating the functional coating slurry on the other surface of the base film and / or the surface of the ceramic coating, drying, obtaining a functional coating, and obtaining a composite diaphragm.

8. The method for preparing the composite diaphragm according to claim 7, characterized in that: In the step 2, the mass ratio of the 2-acrylamide-2-methylpropanesulfonic acid, the azobisisobutyronitrile and the Li2CO3 powder is 60-80:1-5:20-30.

9. The method for preparing a composite diaphragm according to claim 7, characterized in that: In the step 2, the mass concentration of the lithium poly-2-acrylamide-2-methylpropane sulfonate in the solution A is 10% to 50%.

10. The method for preparing a composite diaphragm according to claim 7, characterized in that: In the step three, the mass ratio of the lithium aluminum titanium phosphate, the binder and the lithium poly-2-acrylamide-2-methylpropane sulfonate is 3-5:0.5-2:0.5-2.

Citation Information

Patent Citations

  • Lithium battery diaphragm, lithium battery and preparation method

    CN116014361A

  • Diaphragm, electrode assembly, battery and electric device

    CN118676535A

  • Manufacturing method of porous separator for secondary battery

    KR1020100073894A

  • Composite separator for lithium secondary battery, and lithium secondary battery using the composite separator

    US20160164059A1